Utilizing Social Media Videos in the Discovery Nano Learning Model to Improve Critical Thinking Skills - Sastra Wijaya; Arita Marini; Arifin Maksum (Universitas Majalengka, 2026)
This study aims to analyze the effectiveness of utilizing social media-based learning videos in the discovery nano learning model on improving critical thinking skills of elementary school students. The study was conducted at Walantaka IV Public Elementary School, Serang City, with 30 sixth-grade students as participants. This study used a quantitative approach with a quasi-experimental design through a one-group pre-test post-test design. Data collection was carried out through critical thinking ability tests, student learning activity observation sheets, and documentation of the learning process. The research instruments had been tested for validity and reliability before being used in the study. Data were analyzed using descriptive and inferential statistics with paired sample t-tests to determine differences in students' critical thinking skills before and after the implementation of the learning model. The results showed that the implementation of social media-based learning videos in the discovery nano learning model had a positive effect on improving students' critical thinking skills. In addition, the use of learning videos distributed through social media was able to increase student engagement in the learning process and facilitate more flexible and interactive learning. The findings of this study indicate that the integration of digital technology with innovative learning approaches can be an effective strategy in improving the quality of learning in elementary schools and developing higher-order thinking skills in students.